Formulasi dan Uji Stabilitas Fisik Ekstrak Kulit Buah Kakao (Theobroma cacao L.) pada Sediaan Pasta Gigi sebagai Antibakteri terhadap Streptococcus mutans - Habiburrahim B, Sartini, Nursiah Hasyim, Abdul Rahim (Jurnal Farmasi dan Ilmu Pengobatan, 2016)
A research about formulation and stability evaluation of cocoa fruit peel extract in toothpaste as antibacterial by Streptococcus mutans had been done. The research was aimed to obtain formula of toothpaste which has good physical characteristic and active antibacterial. The extract was be found, made with remaseration of extraction of cocoa fruit peel with menstrume fluid ethanol 70%. The results of quantity analysis of polyphenol within the extract of ethanol 2.25%. The toothpaste made with active compound extract of cocoa fruit peel and gelling agent Na-CMC with variation of concentration 0.5%, 1% and 1.5%. The evaluation formula shows before and after stressed condition storage alternately organoleptic, homogeny, viscosity, pH value measurement and test antibacterial activity against Streptococcus mutans. The results of the study show that before storage Formula H1 and H3 do not quality in reologi of toothpaste, while Formula H2 has good reologi before and after storage. Therefore, the only Formula H2 could be continued into further evaluation. The average pH value also does not change and it has shown 7.68. The results of inhibition zone diameter average are 16.63 mm. The conclusion of research appeal that the cocoa fruit peel extract from three of them that has shown good characteristic was Formula H2 with inhibition zone to bacterial Streptococcus mutans 16.63 mm include in category high activities antibacterial.